The relationship between experiencing physical and emotional-verbal violence and perceived social support with postpartum depression among women - Narges Rahmatollahi; Anahita Khodabakhshi-koolaee; Ladan Mansoor; Taghi Pour-Ebrahim (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Diverse violence against women has several negative effects, especially after partum. Also, social supportive is one of the factors to enhance the mental health during this phase. Therefore, the aim of current study is to investigate the relationship between physical and emotional-verbal violence and social support with postpartum depression among women. Materials and Methods: This research is a descriptive correlational. The population is comprised women with postpartum depression in Tehran city in the years of 2014-15. The 140 women with postpartum depression were selected in a purposed sampling. The measuring instruments are Edinburgh Postnatal Depression (EPDS), Scale methods of conflict in marital disputes (CTS-2) and perceived social support scale multi-dimensional (MSPSS). Data was analyzed utilizing Pearson correlation coefficient and multiple regressions. Results: The results indicated that the relationship of total score of violence rate and postpartum depression are statistically significant (p<0.001), although there is not the significant relationship between the verbal- emotional violence and postpartum depression (p<0.001). Also, the total score of perceived social support and postpartum depression are statistically significant. In addition, violence and perceived social support can be predicted 16.9% and -0.319% of the variance of postpartum depression respectively.               Conclusion: These findings emphasize that violence and lack of social support increase the occurrence of postpartum depression. Hence, it should be considered as risk factors in therapeutic intervention and postpartum depression prevention programs.